2012
DOI: 10.1002/nau.22267
|View full text |Cite
|
Sign up to set email alerts
|

IPSS is lower in hypertensive patients treated with angiotensin‐II receptor blocker: Posthoc analyses of a lower urinary tract symptoms population

Abstract: The IPSS is lower in patients with HT treated with ARB. Other drugs for HT, including ACE-I and CCB, did not improve the IPSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
3
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 19 publications
2
38
3
4
Order By: Relevance
“…[33] In the other study by Ito et al, investigators found CA users had a significantly higher mean score compared to non-treated hypertensive patients. [32] The authors commented that contrary to what they had expected, “sub-scores for intermittency, not for storage symptoms, were worse in patients with CA treatment in this study.” This finding is consistent with that of Hall et al Interestingly, in Ito et al’s study men taking angiotension receptor antagonists were found to have significantly lower IPSSs, yet there were no significant differences in quality of life across the antihypertensive classes.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…[33] In the other study by Ito et al, investigators found CA users had a significantly higher mean score compared to non-treated hypertensive patients. [32] The authors commented that contrary to what they had expected, “sub-scores for intermittency, not for storage symptoms, were worse in patients with CA treatment in this study.” This finding is consistent with that of Hall et al Interestingly, in Ito et al’s study men taking angiotension receptor antagonists were found to have significantly lower IPSSs, yet there were no significant differences in quality of life across the antihypertensive classes.…”
Section: Discussioncontrasting
confidence: 77%
“…The first study of 3790 Japanese men suffering from LUTS looked at the association between LUTS and hypertension. [32] The study revealed that patients on CAs had a statistically significantly higher IPSS 19.6 compared to 18.2 for patients with no treatment for hypertension, p<0.05. Patients on angiotensin receptor blockers scored significantly lower IPSS, while patients on angiotensin converting enzyme (ACE) inhibitors were shown to have scores not significantly different to the no-treatment group.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…12 This fact suggests that angiotensin II receptors play a role in urinary bladder function. The pathophysiological role of angiotensin II in the cardio-vascular system was established in detail.…”
Section: Discussionmentioning
confidence: 99%
“…The lower urinary tract harbors a local renin-angiotensin system [30] that contributes to stress incontinence in animal models [31]. A post hoc analysis of antihypertensive patients treated with AT 1 receptor blockers revealed lesser lower urinary tract symptoms than the untreated subjects [32]. Here, we have demonstrated that blocking AT 1 receptors sensitizes denuded and intact human detrusor to noradrenaline relaxation suggesting that local angiotensin II production counteracts smooth muscle relaxation by noradrenalin and is also involved in blunting the noradrenaline relaxation in the presence of urothelium.…”
Section: Discussionmentioning
confidence: 99%